2018
DOI: 10.1177/016146811812001005
|View full text |Cite
|
Sign up to set email alerts
|

Neglected Issues: How Charter Schools Manage Teachers and Acquire Resources

Abstract: Background/Context Charter schools are commonly discussed as being more effective at matching student and family interests with school mission, ensuring family choice of educational products and improving education quality and the efficiency of resource use as a result of the competitive dynamics they are assumed to generate between themselves and public schools. The rhetoric around charter schools in general puts little attention on teacher management and resource acquisition, and the literature on charter sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…'academies' in the UK) have mainly grown in industrialized countries (such as the USA and Europe) they form a substantial component of the Chilean schooling system (Ávalos and Bellei, 2019) and of others 10.4 .1 .2 across Latin America. A study of charter schools in Bogotá, Colombia (Edwards Jr and Hall, 2018) found that compared to public schools, the managerial exibility of these schools facilitated the use of questionable employment practices: hiring of non-unionized teachers, short-term contracts and lower salaries, despite comparatively lengthy working hours and heavy teaching loads.…”
Section: Professional Status Markets and Accountability Policiesmentioning
confidence: 99%
“…'academies' in the UK) have mainly grown in industrialized countries (such as the USA and Europe) they form a substantial component of the Chilean schooling system (Ávalos and Bellei, 2019) and of others 10.4 .1 .2 across Latin America. A study of charter schools in Bogotá, Colombia (Edwards Jr and Hall, 2018) found that compared to public schools, the managerial exibility of these schools facilitated the use of questionable employment practices: hiring of non-unionized teachers, short-term contracts and lower salaries, despite comparatively lengthy working hours and heavy teaching loads.…”
Section: Professional Status Markets and Accountability Policiesmentioning
confidence: 99%
“…Those of us who study nonprofit organizations have observed with interest the vast increase in the number of civil society organizations providing education to America’s youth through charter schools. Nonprofit scholars have examined this new nonprofit form, their management, governance, and relationship to governments at all levels (Edwards & Hall, 2018; Hill & Lake, 2017; Stahl, 2020). In addition, some have drawn attention to the outsized role philanthropic foundations, such as the Walton Foundation, have played in the spread of charter schools (Carr & Holley, 2014; Dixson et al, 2015; Fabricant & Fine, 2015), explored the role of community-based organizations as advocates for social change in public education (Flynt, 2010; Jha & Beckman, 2017; Milakovich & Wise, 2019), and tracked the increase in parent volunteering as a result of the charter school movement (Flynt, 2010; Oberfield, 2020; Wang & Fahey, 2011).…”
mentioning
confidence: 99%